GAMBARAN TINGKAT KEPUASAN PESERTA DIDIK KEDOKTERAN TERHADAP METODE PEMBELAJARAN KLINIK DI RS PENDIDIKAN IMMANUEL BANDUNG - Nelly Christina Febfriana; Tria Seli Anggraeni; Ceria Febiana (Institut Pendidikan Tapanuli Selatan, 2021)
This research focuses on the satisfaction of Maranatha Christian University students who are conducting clinical learning at the Immanuel Teaching Hospital, Bandung on existing clinical learning methods, in the form of CSC (Clinical Science Studies), CBD (Case Based Discussion), BST (Bed Side Teaching), Mini Lecture, Mini Clinical Exercise (MiniCEX) and DOPS methods. The purpose of this study was to determine: (1) The level of student satisfaction from the given clinical learning (2) The influence of the learning method on the implementation of clinical learning carried out. This research method uses quantitative methods. The population in this study were Maranatha Christian University medical students who were conducting clinical studies at the Immanuel Hospital, Bandung. This study uses random sampling, data collected using questionnaire, with the total sample of 76 subjects. This study tested the hypothesis by using validity and reliability tests. the results of this study have a correlation value of 0.770, which means that there is a very strong correlation between the satisfaction variables of medical students and clinical learning methods. This study addresses two problems: (1). Medical students' dissatisfaction toward current clinical department rotation (2). There has been an implementation of clinical department rotation freeze during the COVID-19 pandemic outbreak in Indonesia.